Evaluation of early childhood social-communication difficulties in children born preterm using the quantitative checklist for autism in toddlers - Wong, H; Huertas-Ceballos, A; Cowan, F; Modi, N; Medicines for Neonates Investigator Group (Elsevier, 2013)
Objectives To characterize early childhood social-communication skills and autistic traits in children born very preterm using the Quantitative Checklist for Autism in Toddlers (Q-CHAT) and explore neonatal and sociodemographic factors associated with Q-CHAT scores. Study design Parents of children born before 30 weeks gestation and enrolled in a study evaluating routinely collected neurodevelopmental data between the post-menstrual ages of 20 and 28 months were invited to complete the Q-CHAT questionnaire. Children with severe neurosensory disabilities and cerebral palsy were excluded. Participants received neurodevelopmental assessments using the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III). Q-CHAT scores of this preterm cohort were compared with published general population scores. The association between Bayley-III cognitive and language scores and neonatal and sociodemographic factors with Q-CHAT scores were examined. Results Q-CHAT questionnaires were completed from 141 participants. At a mean post-menstrual age of 24 months, the Q-CHAT scores of the preterm cohort (mean 33.7, SD 8.3) were significantly higher than published general population scores (mean 26.7; SD 7.8), indicating greater social-communication difficulty and autistic behavior. Preterm children received higher scores, particularly in the categories of restricted, repetitive, stereotyped behavior, communication, and sensory abnormalities. Lower Bayley-III language scores and non-white ethnicity were associated with higher Q-CHAT scores. Conclusions Preterm children display greater social-communication difficulty and autistic behavior than the general population in early childhood as assessed by the Q-CHAT. The implications for longer-term outcome will be important to assess.